Anpassungsrelevante Klimaänderungen für städtische Baustrukturen und Wohnquartiere - Hackenbruch, Julia (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2018)
The influence of climate change on urban heat island intensity is analyzed for the city of Karlsruhe, southwestern Germany. First, its present diurnal and seasonal as well as spatial modes of variability are characterized by means of different meteorological observation datasets. One focus is on temperature differences during heat events. Second, high-resolution regional climate model data allow for projecting the future development of the urban heat island.